2020
DOI: 10.1177/1066896920930100
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Angiosarcoma With C-MYC Amplification Following Prophylactic Bilateral Mastectomy and Autologous Breast Reconstruction: Report of a Case and Review of the Literature

Abstract: In this article, we report a very rare case of secondary angiosarcoma in a young woman with no prior history of breast cancer who had bilateral prophylactic mastectomies with autologous reconstruction due to a strong family history of breast cancer and BRCA1 gene variant of uncertain significance. The surgery was complicated by recurrent fat necrosis requiring several excisions and additional reconstruction followed by the development of localized lymphedema and subsequent angiosarcoma in the reconstructed bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…12 Previous studies have demonstrated MYC amplification in 55% of angiosarcomas secondary to irradiation or chronic lymphedema in a variety of anatomic sites, 13 54% of radiation-associated angiosarcoma of the breast, 14 primary cutaneous angiosarcoma 15 and rarely secondary angiosarcoma following autologous breast reconstruction. 15,16 Amplification of MYC has been hypothesized to be an early event in the pathogenesis of radiation-associated angiosarcoma of the breast, supported by the observation that non-malignant radiationinduced atypical vascular lesions in the breast lack MYC amplification and very rarely progress to angiosarcoma. 17 The prognostic significance of MYC amplification may vary based on the anatomic site, as it has been shown to be associated with a poor prognosis in radiation-associated angiosarcoma 14 but did not appear to correlate with clinical outcome in primary cutaneous angiosarcoma.…”
Section: Discussionmentioning
confidence: 98%
“…12 Previous studies have demonstrated MYC amplification in 55% of angiosarcomas secondary to irradiation or chronic lymphedema in a variety of anatomic sites, 13 54% of radiation-associated angiosarcoma of the breast, 14 primary cutaneous angiosarcoma 15 and rarely secondary angiosarcoma following autologous breast reconstruction. 15,16 Amplification of MYC has been hypothesized to be an early event in the pathogenesis of radiation-associated angiosarcoma of the breast, supported by the observation that non-malignant radiationinduced atypical vascular lesions in the breast lack MYC amplification and very rarely progress to angiosarcoma. 17 The prognostic significance of MYC amplification may vary based on the anatomic site, as it has been shown to be associated with a poor prognosis in radiation-associated angiosarcoma 14 but did not appear to correlate with clinical outcome in primary cutaneous angiosarcoma.…”
Section: Discussionmentioning
confidence: 98%
“…The treatment of AS with c-MYC gene amplification has been discussed in a few case reports[ 20 - 22 ]. In a previous study, patients with radiation-induced abdominal AS exhibited a dramatic response to apatinib[ 23 ].…”
Section: Discussionmentioning
confidence: 99%